The Lords of Aalst in Flanders (10th-12th centuries) : nobles and merchants? - De ruysscher, Dave (Médiévales)
The influence and power of the nobility in the 11th and 12th centuries is often linked to the possession of feudal estates. The example of the Flemish family "de Gand" shows that connections in trade, even international trade, could underlie power. Ownership of domains was built up strategically, along trade routes. The family's support for Flemish towns and presence in Eastern England were linked to the wool trade. The term « noble » appears, in relation to this family, as a designation of belonging to a higher social stratum, even outside a specific activity or expertise. In this respect, the example of the family "de Gand" provides elements to nuance the distinction between the classes of merchants and noblemen.